Violence in the Borderlands of Burkina Faso, Niger, and Benin: Regional Integration Without ECOWAS - Donko, Kamal; Doevenspeck, Martin (Society, 2025)
The article examines how communities in the tri-border region of Burkina Faso, Niger, and Benin manage security and cooperation after the weakening of Economic Community of West African States (ECOWAS) and the rise of the Alliance of Sahel States (AES). Using interviews, observations, and social network analysis, the study reveals that, in the absence of strong state or regional authority, local actors—such as chiefs, market women, religious leaders, and youth groups—develop their hybrid systems for resolving disputes, ensuring security, and managing cross-border trade. While these informal and locally rooted arrangements often fill gaps left by formal institutions and can be effective and innovative, they also have serious limitations. They may exclude outsiders, reinforce old hierarchies, and sometimes escalate tensions or insecurity. Digital tools like WhatsApp are increasingly important, but access is unequal. The article argues that real regional integration and security depend on recognizing and supporting these local practices, while also addressing their shortcomings and not just relying on top-down solutions from organizations like ECOWAS. The experience of these borderlands challenges traditional ideas about borders and governance, showing that both resilience and vulnerability coexist in complex ways.